Contenido de materia orgánica y biodegradabilidad en aguas residuales: aportes desde la validación de los métodos analíticos demanda química de oxígeno y demanda bioquímica de oxígeno - Castro Narváez, Sandra Patricia (Universidad Santiago de Cali, 2020)
The validation of the Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) was carried out. In the first, a potassium acid phthalate standard and a spectrophotometric detection method were used, and for the second, the reading of samples was implemented by membrane electrode, a standard glutamic acid-glucose solution and incubation for 5 days at 20 ± 1ºC. Parameters were determined as linearity, precision, accuracy, sensitivity, limit of detection and quantification. It was demonstrated through experimental design and statistical procedures that methods can be used with sensitivity and confidence. Detection and quantification limits of 46.2 and 100 mg/L for COD and 2.78 and 4.71 mg / L for BOD were reached. In both tests a coefficient of variation for repeatability and reproducibility between 0.001 - 0.055% and 0.001 - 0.022% was evidenced; in accuracy, error and recovery percentages were obtained between 0.04 - 3.39% and 95.0 and 103% respectively.